"What are you doing to us?!": mediating English-only policies to sustain a bilingual education program. Issue 4 (2nd October 2022) - Sánchez, Maite T.; Menken, Kate; Pappas, Liza N.
ABSTRACT: Although U.S. schools that provide bilingual education typically must negotiate English-only policies and pressures to sustain their programming over time, little is known about what this entails at the individual school level. Our research examines in detail how the leaders of an elementary school in New York City with a Spanish-English transitional bilingual education program navigated a range of language education policies over a five-year period. We found that federal, state, and school district policy mandates for English literacy instruction during those years resulted in the imposition of English-only curricula on the school, which undermined its bilingual education program. We identified the following three stages in the school's efforts to mediate those policies: (1) establishing a vision for biliteracy, (2) (barely) surviving English-only literacy reforms, and (3) restoring and advancing the vision for biliteracy. These findings shed light on the work of school leaders and educators to maintain bilingual education programs in U.S. schools and, in the absence of coherent language policies that truly support the implementation of bilingual education, highlight the need for school leaders and educators to establish a clear vision and receive ongoing targeted supports to be able to negotiate policy mandates.